Rates of Holocene normal faulting along the Dong Co fault in central Tibet, based on 14C dating of displaced fluvial terraces. (1st October 2019) - Li, Kang; Kirby, Eric; Xu, Xiwei; Chen, Guihua; Ren, Junjie; Wang, Duo
Graphical abstract: Highlights: Vertical slip rates along the Dong Co fault are determined from 14 C dating of displaced fluvial terraces. The average normal faulting vertical rate is 0.7 +0.3/−0.2 mm/yr since 3.9–6.3 ka. Motion along the Dong Co fault reflects crustal extension and thinning in central Tibet. Abstract: Crustal extension along north-south graben characterizes active deformation within the central Tibetan Plateau. However, the geodynamic significance of these fault systems remains uncertain, in part reflecting sparse data regarding the onset of extension, rate(s) of slip, and paleoseismic histories along these faults. The Dong Co fault is located to the north of the dextral Beng Co fault in central Tibet. Based on the interpretation of satellite images, we use unmanned aerial vehicle (UAV) topographic surveying and 14 C dating of two offset fluvial terraces to characterized active slip along the Dong Co fault of 1.2 +0.3/−0.3 m and 3.7 +0.5/−0.4 m during the past 550–1060 yr BP and 3880–6290 yr BP, respectively. These results indicate that the slip rate of the Dong Co fault during the latter half of the Holocene has been 0.7 +0.3/−0.2 mm/yr. Fault displacement and scaling relationships imply that the most recent earthquake was approximately Mw ~ 7.0. Together with the dextral Beng Co fault system, the Dong Co fault appears to record stretching of a wedge-shaped domain bounded by conjugate strike-slip faults. Our study supports models in which extension along normal faults can accommodate differential stretching between conjugate strike-slip faults.